Letter from Malvina C. Thompson to Edwin M. Ross - Thompson, Malvina (1939)
Letter from Malvina C. Thompson (secretary to First Lady Eleanor Roosevelt) to Edwin M. Ross instructing him that the samples of water fabricated by Betz Laboratories to duplicate London City water has arrived. Mrs. Roosevelt requested five gallons of the water to be delivered to the White House to be used to serve tea to the King and Queen of England.
Keywords: Betz Laboratories, Inc.; Water--Analysis; Drinking water; Roosevelt, Franklin D. (Franklin Delano), 1882-1945; Roosevelt, Eleanor, 1884-1962; Elizabeth, Queen, consort of George VI, King of Great Britain, 1900-2002; George VI, King of Great Britain, 1895-1952; United States. Office of the First Lady; Presidents